Inhibitory Effect of Aqueous Garlic (Allium sativum) Bulb Extract on Growth and Physiological Response Dynamics of Two Palm Species - Setiyanto, Afif Eka Rahma; Nashafi, Azizuddin Muhammad; Turhadi, Turhadi; Siswanto, Dian (Universitas Negeri Semarang, 2025)
The Merrill palm (Adonidia merrillii) and the Yellow palm (Dypsis lutescens) are hosts of various pests. Garlic (Allium sativum) phytochemicals are applied as a phytopesticide and affect the plant host as well. On the other hand, studies related to garlic phytochemicals' effect on these palms are limited. The present study was conducted to explore the effect of aqueous garlic bulb extract (AGBE) on the Merrill palm and the Yellow palm on those physiological dynamics and growth responses to apply the best concentration as a phytopesticide and observe the palm performance. AGBE is conducted by maceration and application by spraying. Variation AGBE concentrations were 12.5 g/100 mL, 25 g/100 mL, and 50 g/100 mL. The results revealed the profiles of the two palms were different, causing significant differences in growth, in which the Merrill palm was taller while Yellow palm greater leaf number increase; physiological response of two palms was not differing significantly on carbon dioxide concentration but differ significantly on stomatal opening percentage in 28 DAS (day after spraying) and chlorophyll content in 56 DAS; AGBE 25 g/100 mL suppress height increase significantly but leaf number increase not affected; AGBE did not influenced significantly on carbon dioxide, AGBE 50 g/100 mL significantly influenced on stomatal opening in 42 and 56 DAS but chlorophyll not significantly different, overall AGBE tend to inhibit all physiological response. This study concludes that AGBE concentrations in the current study are not recommended as a phytopesticide on both palms due to all concentrations generally inhibiting the growth and physiological response of these palms.